2020
DOI: 10.1039/d0gc02763d
|View full text |Cite
|
Sign up to set email alerts
|

Expeditious and sustainable two-step synthesis of sinapoyl-l-malate and analogues: towards non-endocrine disruptive bio-based and water-soluble bioactive compounds

Abstract: Straightforward and sustainable two-step route to bioactive sinapoyl-l-malate and analogues using Meldrum's acid opening and Knoevenagel-Doebner condensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Several works have shown that SADs can be used as antioxidant molecules for different applications [ 3 , 35 , 36 ]. Figure 4 shows the antioxidant activity of the various extracts, measured by the DPPH radical scavenging method, expressed in mg of Trolox equivalent per 100 g DM .…”
Section: Resultsmentioning
confidence: 99%
“…Several works have shown that SADs can be used as antioxidant molecules for different applications [ 3 , 35 , 36 ]. Figure 4 shows the antioxidant activity of the various extracts, measured by the DPPH radical scavenging method, expressed in mg of Trolox equivalent per 100 g DM .…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of a broad range of Gram-negative and Gram-positive bacteria have also been demonstrated using a SinA fraction isolated from the ethanolic extract of rapeseed (Nowak et al, 1992). The antimicrobial activities of sinapine (Mouterde et al, 2020) and other SinEs (Peyrot et al, 2020b) against Escherichia coli have also been recently highlighted. These literature reports strongly suggest that SinA and its derivatives are potential biobased antimicrobial reagents.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Although pure final product was obtained with a decent yield, the extensive use of toxic solvents along with multiple protection/deprotection steps throughout the pathway will likely hinder of the application of this approach at multigramscales. With this in mind, Peyrot et al have devised a more sustainable and straightforward, protecting group-free procedure based on the Knoevenagel-Doebner condensation of syringaldehyde (12) and malic monomalonate ester (Figure 15) (Peyrot et al, 2020b). Sinapoyl malate and analogues were thereby obtained in higher yields.…”
Section: Sinapoyl Glucosementioning
confidence: 99%
See 2 more Smart Citations